HISTOMORPHOLGICAL STUDY OF THE PARATHYROID GLAND OF ONE-HUMPED CAMEL (CAMELUS ‎DROMEDARIUM)‎ - S. Al-Samaraee‎, N.; A. Khamas ‎, W.; Y. Dakeel‎, J. (The Iraqi Journal of Veterinary Medicine, 1987)
Parathyroid gland of ten adult one-humped came] has been collected from the slaughter house. Glands have been fixed sectioned and stained by several procedures. The gland measured 1.2 cm in length, 0.4 cm in width and 0.25 cm thick. It differs in position from left to right side due to displacement of thyroid gland. The gland consisted of aggregate of cells arranged as solid masses, clusters, cords or strands. The parenchyma of the gland appeared with different cell density. Four cell type has been distinguished, viz., light as well as dark chief cells, oxyphils and syncytial cells.